NORMA HUKUM DAN BISNIS TANGGUNG JAWAB SOSIAL PERUSAHAAN - Siti Kusumawati Azhari (Jurnal Sosioteknologi, 2007)
Company social responsibility is stated under the Environmental Laws which is based on sustainability and benefit to develop and enhance the partnership among the community, entrepreneurs, and company for the purpose of maintaining the land capacity and environment. While the community has its role and opportunity to manage the environment, the government has a role to set rules concerning the company social responsibility in accordance with the articles of Indonesia's 1945 Constitution, religion values, customs, and beliefs in the society. Those involved in the dispute can voluntarily choose either settle their dispute through court or arbitration.